Al-Umma: Reform, Resistance, and the Periodical’s Role in Pan-Islamic Thought - Emara, Nagat (Oriente Moderno, 2025)
Abstract This paper explores alternative political imaginaries, envisioned communities, and forms of resistance as articulated in the Arabic newspaper al-Umma: ǧarīda ʿarabīyya taṣduru kull yawm ǧumʿa (Al-Umma: An Arabic Newspaper published every Friday), published and edited by Sheykh Abū al-Yaqẓān (d. 1973), a former student of the Ibadite reformist scholar Muḥammad Aṭṭfiyaš (d. 1914), in Algiers in 1933. It examines how the periodical fashioned itself as an embodiment of the umma (nation) and how its readership formed a community around it. This analysis draws on Jutta Ernst and Oliver Scheiding’s perspective on periodicals, which posits that they function as assemblages that transcend their physical form, becoming expressions of social networks and communities. Focusing on the periodical’s characteristics and features, its language, editorials, symbols, and calls to action, the paper demonstrates how al-Umma was transformed into a subject associated with the umma for its readers. Using Birgit Meyer’s concept of aesthetic formations as a framework, this paper investigates how the newspaper helped construct and embody a pan-Maghrebian identity in 1930s Algeria, beyond the notion of a fixed, bounded social entity.
Keywords: Journalisme – Mzab; Réformisme – Mzab

Islam, réforme et colonisation: une histoire de l'ibadisme en Algérie, 1882-1962 - Jomier, Augustin (Éditions de la Sorbonne, 2020)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

الذكرى الأربعين لشيخ الصحافيين الجزائريين أبي اليقظان (نشيد) - مصلح, أحمد بن مهني (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Poésie – Djerba; Réformisme – Mzab

ذكرى عظيم في الطريق المستقيم - أطفيش, محمد بن محمد بن محمد (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Poésie – Mzab; Réformisme – Mzab

أبو اليقظان في الماضِين رمز - دواق, سليمان بن عمر (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Poésie – Mzab; Réformisme – Mzab

بين الشيخ سليمان الباروني باشا وأبي اليقظان إبراهيم بن عيسى - بن سعدون, المنير بن عبد الحميد (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Bārūnī; Sulaymān al- (1870-1940); Journalisme – Mzab; Réformisme – Mzab

مراسلات الشيخ علي يحيى معمر مع شيخه أبي اليقظان إبراهيم - الشيباني, سليمان بن سعيد (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Muʿammar; Ali Yahya (19XX-1984); Réformisme – Mzab

الروابط الفكرية بين سليمان باشا الباروني وأبي اليقظان - مشيخي, هادية صالح (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Bārūnī; Sulaymān al- (1870-1940); Journalisme – Mzab; Réformisme – Mzab

التواصل بين الجزائر وعمان في صحافة الشيخ أبي اليقظان (أكتوبر 1926- أوت 1938) - جهلان, محمد بن أحمد (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Relations – Oman – Mzab; Réformisme – Mzab

منهج الشيخ أبي اليقظان في التأليف الفقهي التعليمي "سلم الاستقامة" أنموذجا - أرشوم, مصطفى بن حمو (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

دراسة في "فتح نوافذ القرآن" للشيخ إبراهيم أبي اليقظان - الشيهاني, حمو بن عيسى (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

جمالية شعر أبي اليقظان الوطني بين سمو الفكرة وفنية الصورة - بن مخلوف, يحيى; دوادي, زينب (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

الصورة النصية الوصفية عند أبي اليقظان: قراءة في البعد الدّلالي - السليماني, عيسى بن محمد (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

جهاد الشيخ أبي اليقظان الصحفي من خلال أشعار عمر بن عيسى بلعيد البرياني - حاج المحمد, يحيى (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Poésie – Mzab; Réformisme – Mzab

مواقف الشّيخ أبي اليقظان من القضايا الإسلاميّة - مصلح, أحمد بن مهني (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

روح التحدي في صحافة الشيخ أبي اليقظان - حمدي, محمد بن صالح (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

الألم في فكر الشيخ إبراهيم أبي اليقظان ومسيره - بوحجام, محمد بن قاسم ناصر (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

شخصية الإعلامي "إبراهيم أبو اليقظان بن عيسى" من خلال صحافته الحرّة - حين تتحول الصّحافة إلى مرآة عاكسة لنور الإسلام - [1367-1306ه / 1973-1888م] - عيساوي, أحمد (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

حياة نضال - الطالبي, عمار (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

معالم الفكر الإصلاحي عند الشّيخ أبي اليقظان من خلال جريدة وادي ميزاب - باحامد, إدريس بن بابه (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

الشيخ أبو اليقظان ومسالكه المنتجة للإصلاح - الباروني, سناء مهني (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

دور صحافة الشيخ أبي اليقظان في التمكين للمشروع الإصلاحي بالجزائر - الشيخ بالحاج, قاسم بن أحمد (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

الشيخ أبو اليقظان وحركة الإصلاح في العالم العربي - عويمر, مولود (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

الشيخ أبو اليقظان ودوره في الحركة الإصلاحيّة ومكانته في جمعية العلماء المسلمين الجزائريين - ناصر, محمد صالح (ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة, 2020)
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

ملتقى الذكرى الأربعين لوفاة شيخ الصحافة الجزائرية الشيخ إبراهيم ابن عيسى حمدي أبي اليقظان: يومي السبت والأحد 28-29 ذي الحجة 1434 هـ/02-03 نوفمبر 2013 م، المحمدية، الجزائر العاصمة - بوحجام, محمد بن قاسم ناصر (جمعية التراث, 2020)
يعرض هذا الكتاب أعمال الملتقى، الذي أقيم بمناسبة مرور أربعين عامًا على وفاة شيخ الصحافة الجَزائريّة، الشيخ إبراهيم بن عيسى حمدي أبي اليقظان.. مع ما يعرضه من أعمال الملتقى، هو يسجل وينقل إحدى الخطوات الأولى في نشاط مؤسّسة الشيخ أبي اليقظان التّقافيّة، التي نرجو أن تكون لها مشروعات كبيرة في نشر تراث الشيخ إبراهيم أبي اليقظان، والقيام بأعمال علميّة وتنشيط حلقات فكريّة، وإقامة ندوات ثقافيّة، والتّعريف بالشخصيّات الفاعلة في الحقل العلمي بكل فروعه.. وإبراز المشهد الثّقافي بقوّة في الميدان.
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab; Réformisme – Mzab

‏مقالات الشيخ عدون في الصحافة الوطنية - بكوش, محمد بن موسى (جمعية التراث, 2024)
Keywords: Journalisme – Mzab; Réformisme – Mzab

مقالات الإمام بيوض إبراهيم بن عمر في الصحافة الوطنية - بكوش, محمد بن موسى (جمعية التراث, 2023)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Mouvement national – Mzab; Réformisme – Mzab

“There is no sin in it, unless ...”: Legal reform among the Maghreb Ibāḍīs - Vikør, Knut S. (Between Morocco and Indonesia and beyond: Essays in honour of Irene Schneider, 2024)
Keywords: Réformisme – Mzab

Al-Umma Al-Yaqzaniyya’s Self-Representation: A Key to Understanding Algerian Reformism - Emara, Nagat (2024)
Keywords: Journalisme – Mzab; Réformisme – Mzab

Society and Religion in 20th Century Algeria : Ibadite Reform, Between Modernization and Conservation - Salhi, Mohamed Brahim (Insaniyat / إنسانيات. Revue algérienne d'anthropologie et de sciences sociales, 2024)
Ibadite religious reform in the M’zab, is precocious and internal. It starts from the established fact that the Ibadite rite in its initial version doesn’t correspond to the demands imposed by XXth C changes. In this sense it is closer to, the renaissance (Nahda) which germed in the orient at the end of the 19th C early 20th C. It shares many principles with the Badissian reform to which it is allied.However, the Ibadite community’s particularity, imposes the respect of community preservation on its reformers .It also finds there a powerful factor for legalizing to captivate innovations for economic and material modernization. The advancement of the religious reform doesn’t happen without offending conservators of the rite in its purity and its references judged as untouchable.This contribution intends to draw a picture which shows how little by little this reform is outlined, takes shape then takes root, opening an alternative, adapting to change, which is captivated and used as a conservation tool by this particular community.
Keywords: Réformisme – Mzab

The rise of an Ibadi religious revival movement and its impacts on the society and built environment in the Mzab (Saharan Maghrib, 1868-1914) - Kwan, Elisabeth (University of Cambridge, 2024)
This study is about the rise of a nineteenth century religious renewal movement among Ibadi Mzabis, a sectarian and Saharan community. It looks at how this group responded to the local effects of a re-globalising world and redefined its sectarian identity to strengthen itself. The movement, which I call the Ibadi Mzabi *nahḍa*, began in the late 1860s when the community was faced with multiple pressures leading to social division. A cosmopolitan network of merchant-scholars drew on ideas which were circulating among broader Arab-Muslim cultural, intellectual and other religious *nahḍa* movements at the time. Some of these ideas shaped the way in which this local movement was expressed in its textual and built works. During a period of pressure in the 1870s and 1880s, there was a rise in the production of new texts. Through these new texts, there was a renewal of Ibadi religious law and rise in the authority of Ibadi religious scholars, and an increasing recognition that Mzabis were Ibadis rather than Kharijis. In Ghardāya, this rise in sectarianism resulted in the suppression of religious diversity in the public sphere and encouraged the integration of Muslims of multiple identities into a common and "renewed" Ibadi Mzabi community. During a period of prosperity and stability in the late 1890s, new commemorative shrines were built as part of this Ibadi Mzabi *nahḍa*. Through these shrines, new ideas of sectarian identity were expressed in the landscape, substantiating the historical legacy of contemporary Ibadi scholars and expressions of Ibadism in the Mzab.
Keywords: Réformisme – Mzab

المشروع الإصلاحي في وادي ميزاب، الإنجازات والتحديات - الشيخ بالحاج, قاسم بن أحمد (2024)
Keywords: Réformisme – Mzab

الشيخ محمد ارشوم ومنهجه في الإصلاح الاجتماعي - بعوشي, عبد الله بن باعلي (2024)
Keywords: Réformisme – Mzab

A l'ombre de la nation, les continuités inattendues de l'historiographie mozabite dans les années 1960-1970 - Jomier, Augustin (2024)
Keywords: Réformisme – Mzab

الشيخ بيوض كاتبا صحفيا - بكوش, محمد بن موسى (2024)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Journalisme – Mzab; Réformisme – Mzab

Quelle voix pour un réformiste ibadite dans l'entre-deux-guerres ? Abû Ishâq Atfayyish et la rédéfinition de l'identité ibadite (1923-1939) - Cernon, Baudouin de (2023)
Keywords: Aṭfiyyash; Ibrāhīm b. Muḥammad (1886-1965); Réformisme – Mzab

Ibrahim Bayyud (1899-1981). Un guide pour les ibadites d'Algérie - Jomier, Augustin (Savants musulmans au Maghreb, 2023)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

العلاقات المتبادلة بين الأغواط وغرداية زمن الحركة الإصلاحية - خبزي, موسى بن محمد (الحياة, 2022)
Keywords: Réformisme – Mzab

Abū Isḥāq Aṭfayyiš eṭ la redéfinition de l’identité ibadite dans l’entre-deux guerres (1923-1939) : réformisme, communauté et pouvoir - Cernon, Baudouin de (Inalco, 2022)
Keywords: Aṭfiyyash; Ibrāhīm b. Muḥammad (1886-1965); Réformisme – Mzab

Religious and political authority among the Ibadis of Sahara: Not Sunni, not Arab, but Algerian? - Vikør, Knut S. (2022)
In the Sahara, the oasis of Mzab is the home of a small minority of Berber-speaking Muslims, the Ibadis. Long time isolated, they were for the first time integrated into what became “Algeria” with French colonialism. This raised the challenge for the religious and worldly authorities of the community: Should they resist integration into the new larger entity, or should they join in a wider, national struggle for Islamic renewal? How should they relate to the foreign, French authorities? This seminar will place the Mzab in Ibadi history, and trace how the community responded to these challenges during the twentieth century.
Keywords: Réformisme – Mzab

المرشدة عويشي بنت محمد بابكر ودورها في الإرشاد الديني والإصلاح الاجتماعي - مصباح, إبراهيم بن بنوح; بابكر, عبد الله بن بيوض (2022)
Keywords: Réformisme – Mzab

Mariage et sexualité dans les fetwas d’Ibrāhīm Bayyūḍ (1899–1981) - Benkheira, Mohammed Hocine (Studi Magrebini, 2021)
Abstract Ibrāhīm Bayyūḍ is a major figure in both contemporary Algerian Ibāḍism and “reformism”. The study of his fatwas is instructive from this point of view: it can help to better understand the specificities of Algerian Ibāḍism, closely articulated to a “traditional” Berber-speaking society, and inserted in spite of everything into a larger national context. This study can also help to better understand the continuity of a religious culture as well as of an ancient ethical model that the endogenous modernization, which accelerated after Independence, has hardly undermined.
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

الإصلاح وأثره في مبدأ الوطنية من خلال كتابات الشيخ محمد علي دبوز، ترجمته للعربي التبسي ومبارك الميلي وابي اليقظان مناذجا - تمزغين, محمد (2020)
Keywords: Réformisme – Mzab

Algérie. Les ibadites, penseurs de la réforme de l’islam - Sereni, Jean-Pierre (Orient XXI, 2021)
L’historien Augustin Jomier a étudié les évolutions doctrinaires des oulémas ibadites implantés à la fin du XIXe siècle dans les communautés berbères du nord du (...)
Keywords: Réformisme – Mzab

The Politics of Islamic Reform (Iṣlāḥ) in Colonial Algeria: Ibadi Reformism in the 20th Century - Jomier, Augustin (2021)
Keywords: Réformisme – Mzab

Les Oulémas et réformistes musulmans en Algérie : une histoire à redécouvrir (2021)
Les Oulémas et réformistes musulmans en Algérie : une histoire à redécouvrir Charlotte Courreye, Augustin Jomier, Ismaïl Warscheid : trois jeunes historiens nous invitent à redécouvrir l'histoire des oulémas et des réformistes musulmans au prisme de l'histoire plutôt que de l'État.
Keywords: Réformisme – Mzab

Une histoire de l'Algérie par les sources arabes - Guichard, Benjamin (2020)
[Un livre, des collections] Rencontre avec Augustin Jomier, auteur du livre Islam, réforme, colonisation : une histoire de l'ibadisme en Algérie (1882-1962) En partenariat avec les Éditions de la Sorbonne Comment écrire une histoire des temps coloniaux à partir de points de vue d'Algériens et comment penser le réformisme musulman, problème majeur de l'histoire contemporaine de l’islam ? C’est à ces deux questions connexes, aussi centrales qu’irrésolues, que s’attaque simultanément Augustin Jomier dans son étude sur l’ibadisme contemporain, qui vient de paraître aux Éditions de la Sorbonne. La rencontre sera animée par Benjamin Guichard, directeur scientifique de la BULAC, qui présentera en préambule les collections ibadites de la BULAC. L'intervenant : Docteur et agrégé d’histoire, ancien élève de l’École normale supérieure de Lyon, Augustin Jomier a enseigné aux universités du Mans, de Paris-Est-Créteil, à l’EHESS et à l’EPHE. Il a été pensionnaire de la Fondation Thiers (2013-2016), puis lauréat d’une Chaire d’excellence de l’Université Sorbonne-Paris-Cité (2016-2019) et Visiting research fellow au Near Eastern Studies Department de l’Université de Princeton, USA (2018). Il est actuellement maître de conférences à l’Inalco en histoire du Maghreb aux périodes moderne et contemporaine et chercheur au CERMOM. À la jonction entre l’histoire coloniale et l’histoire de l’islam, il s’intéresse aux mutations sociales et culturelles du Maghreb à la période contemporaine, histoire qu’il écrit à partir de sources en langue arabe et en langues européennes. Son premier livre, Islam, réforme et colonisation : une histoire de l’ibadisme en Algérie (1882-1962), Paris, Éditions de la Sorbonne, 2020, enquête sur la question du réformisme musulman parmi les populations ibadites du Mzab, dans l’Algérie coloniale. Le chantier principal auquel il s’attèle à présent porte sur l’histoire sociale et culturelle du livre et de la lecture au Maghreb (XVIIIe-XXe siècle). Il est aussi investi dans un projet intitulé « L'orientalisme en train de se faire », mené à l'EHESS autour des archives de René Basset (1855-1924), fonds d’archives dont il est le responsable scientifique.
Keywords: Réformisme – Mzab

Le Maghreb par les textes: XVIIIe-XXIe siècle - Courreye, Charlotte; Jomier, Augustin; Lacroix, Annick (Armand Colin, 2020)
Lettre d’un « indigène israélite » du Mzab Le séjour du savant marocain al-‘Ayyāshī à Ouargla (ca 1650) Inspection d’une école musulmane réformiste dans le Sud algérien, 1944 Les conseils d’un lettré algérien à des Libyens, 1934
Keywords: Réformisme – Mzab

Chemins d'histoire (Radio Clype)-Le Maghreb, C. Courreye, A. Jomier, A. Lacroix, 13.09.20 - Courreye, Charlotte; Jomier, Augustin; Lacroix, Annick (2020)
Quarante-troisième numéro de Chemins d'histoire, l'émission d'histoire de Radio Clype, premier numéro de la deuxième saison, émission réalisée par Margot Leutard, animée par Luc Daireaux Émission diff
Keywords: Réformisme – Mzab